Does Language Matter? Exploring Chinese–Korean Differences in Holistic Perception - Rhode, Ann K.; Voyer, Benjamin G.; Gleibs, Ilka H. (Frontiers in Psychology, 2016)
Cross-cultural research suggests that East Asians display a holistic attentional bias by paying attention to the entire field and to relationships between objects, whereas Westerners pay attention primarily to salient objects, displaying an analytic attentional bias. The assumption of a universal pan-Asian holistic attentional bias has however recently been challenged in experimental research involving Japanese and Chinese participants, which suggests that linguistic factors may contribute to the formation of East Asians’ holistic attentional patterns. The present experimental research explores differences in attention and information processing styles between Korean and Chinese speakers, who have been assumed to display the same attentional bias due to cultural commonalities. We hypothesize that the specific structure of the Korean language predisposes speakers to pay more attention to ground information than to figure information, thus leading to a stronger holistic attentional bias compared to Chinese speakers. Findings of the present research comparing different groups of English, Chinese, and Korean speakers provide further evidence for differences in East Asians’ holistic attentional bias, which may be due to the influence of language. Furthermore, we also extend prior theorizing by discussing the potential impact of other cultural factors. In line with critical voices calling for more research investigating differences between cultures that are assumed to be culturally similar, we highlight important avenues for future studies exploring the language-culture relationship.